The redox status of salinity-stressed Chenopodium quinoa under salicylic acid and sodium nitroprusside treatments - Hajihashemi, Shokoofeh; Jahantigh, Omolbanin; Alboghobeish, Sahira (Frontiers in Plant Science, 2022)
Spreading the cultivation of crops with high nutritional values such as quinoa demands a wide area of research to overcome the adverse effects of environmental stress. This study aimed at investigating the role of salicylic acid (SA) and sodium nitroprusside (SNP) as a nitric oxide donor, priming at improving the antioxidant defense systems in boosting salinity tolerance in Chenopodium quinoa. These two treatments, SA (0.1 mM) and SNP (0.2 mM), individually or in combination, significantly improved the function of both enzymatic and non-enzymatic antioxidants. SA and SNP priming significantly reduced superoxide dismutase activity, which was accompanied by a significant decrease in hydrogen peroxide accumulation under salinity stress (100 mM NaCl). The SA and SNP treatment increased the activity of enzymatic antioxidants (e.g., catalase, ascorbate peroxidase, peroxidase, and glutathione reductase) and the accumulation of non-enzymatic antioxidants (e.g. ascorbate–glutathione pools, α-tocopherol, phenols, flavonoids, anthocyanins, and carotenoids) to suppress the oxidative stress induced by salinity stress. Under SA and SNP treatment, the upregulation of antioxidant mechanisms induced a significant increase in chlorophyll florescence, chlorophylls, carotenoids, and proteins, as well as a significant reduction in the malondialdehyde content in salinity-stressed plants. In addition, the foliar application of SA or/and SNP led to a significant increase in the accumulation of osmoprotectant molecules of sugars and proline to overcome osmotic stress induced by salinity stress. In conclusion, SA and SNP priming can effectively combat salinity stress through improving the redox status of plants.